Perivascular Stem Cells Diminish Muscle Atrophy Following Massive Rotator Cuff Tears in a Small Animal Model. (15th February 2017) - Eliasberg, Claire D.; Dar, Ayelet; Jensen, Andrew R.; Murray, Iain R.; Hardy, Winters R.; Kowalski, Tomasz J.; Garagozlo, Cameron A.; Natsuhara, Kyle M.; Khan, Adam Z.; McBride, Owen J.; Cha, Peter I.; Kelley, Benjamin V.; et al.
Abstract : Background: Rotator cuff tears are a common cause of shoulder pain and often necessitate operative repair. Muscle atrophy, fibrosis, and fatty infiltration can develop after rotator cuff tears, which may compromise surgical outcomes. This study investigated the regenerative potential of 2 human adipose-derived progenitor cell lineages in a murine model of massive rotator cuff tears. Methods: Ninety immunodeficient mice were used (15 groups of 6 mice). Mice were assigned to 1 of 3 surgical procedures: sham, supraspinatus and infraspinatus tendon transection (TT), or TT and denervation via suprascapular nerve transection (TT + DN). Perivascular stem cells (PSCs) were harvested from human lipoaspirate and sorted using fluorescence-activated cell sorting into pericytes (CD146 + CD34 − CD45 − CD31 − ) and adventitial cells (CD146 − CD34 + CD45 − CD31 − ). Mice received no injection, injection with saline solution, or injection with pericytes or adventitial cells either at the time of the index procedure ("prophylactic") or at 2 weeks following the index surgery ("therapeutic"). Muscles were harvested 6 weeks following the index procedure. Wet muscle weight, muscle fiber cross-sectional area, fibrosis, and fatty infiltration were analyzed. Results: PSC treatment after TT (prophylactic or therapeutic injections) and after TT + DN (therapeutic injections) resulted in less muscle weight loss and greater muscle fiber cross-sectional area than was demonstrated for controls (p < 0.05). The TT + DN groups treated with pericytes at either time point or with adventitial cells at 2 weeks postoperatively had less fibrosis than the TT + DN controls. There was less fatty infiltration in the TT groups treated with pericytes at either time point or with adventitial cells at the time of surgery compared with controls. Conclusions: Our findings demonstrated significantly less muscle atrophy in the groups treated with PSCs compared with controls. This suggests that the use of PSCs may have a role in the prevention of muscle atrophy without leading to increased fibrosis or fatty infiltration. Clinical Relevance: Improved muscle quality in the setting of rotator cuff tears may increase the success rates of surgical repair and lead to superior clinical outcomes.